Nutritional antioxidant potential of Spondias mombin against ibuprofen-induced hepatotoxicity in rats - Efosa Bolaji Odigie; Blessing Emosho Ogeyemhe (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada, 2026)
Background: Drug-induced liver injury is a significant clinical problem, especially in the context of widespread use of nonsteroidal anti-inflammatory drugs (NSAIDs). It is often associated with oxidative stress, prompting interest in nutritional antioxidants from medicinal plants as protective agents.Objective: This study aims to investigate the nutritional antioxidant potential of Spondias mombin stem bark extract in mitigating Ibuprofen-induced oxidative liver injury in Wistar rats.Methods: Thirty Wistar rats were randomly allocated into six groups (n = 5). Hepatotoxicity was induced using ibuprofen (20 mg/kg), while S. mombin stem bark extract (1,000 mg/kg) was administered alone, with ibuprofen, as pre- and post-treatment for 14 days. Blood samples were analyzed for liver enzymes, bilirubin, proteins, cholesterol, coagulation parameters, and inflammatory cytokines (TNF-α, IL-6). Liver tissues were evaluated for oxidative stress markers including malondialdehyde, superoxide dismutase, catalase, glutathione, glutathione peroxidase, and total antioxidant capacity. Histological and histochemical analyses were performed using H&E and PAS staining. Data were expressed as mean ± SD and analyzed using one-way ANOVA with Tukey’s test in SPSS (p < 0.05).Results: Ibuprofen administration was associated with increased liver enzymes, bilirubin, cholesterol, PT/INR, tumor necrosis factor-alpha, interleukin-6, and malondialdehyde, along with decreased antioxidant enzymes, albumin, and total proteins. The extract was able to restore all the abnormalities, reducing liver enzyme leakage, cytokines, oxidative stress, and enhancing liver protein synthesis. Histology revealed severe liver damage with ibuprofen, while the extract groups showed significant improvement in histology, including glycogen distribution.Conclusion: Spondias mombin stem bark extract effectively mitigated ibuprofen-induced oxidative liver injury in Wistar rats, likely through its antioxidant and anti-inflammatory activities.